ChemInform Abstract: A Ce(OTf)3/PyBox Catalyzed Enantioselective Hosomi—Sakurai Reaction of Aldehydes with Allyltrimethylsilane. Issue 6 (21st January 2016) - Zhao, Song; Zhang, Xulong; Zhang, Yuwei; Yang, Huanhuan; Huang, Yan; Zhang, Kui; Du, Ting
Abstract: Homoallylic alcohols are efficiently synthesized in good yields and excellent enantioselectivities using chiral complexes as catalysts.